Time-dependent evolution of grout buoyancy in shield tunnel backfill grouting: A fluid–solid phase transition perspective - Shaolong Duan; Qingsong Zhang; Yu Wu; Huasheng Zhang; Yueji He; Zunchao Ren; Xianghui Li (Tunnelling and Underground Space Technology, 2026)

Simultaneous aridification of soil moisture driven by anthropogenic activities in China’s loess critical zone - Meng Ren; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Changfeng Sun; Xiangyu Duan; Zekun Hu (Journal of Hydrology, 2026)

Terroir-associated variations in anthocyanin and proanthocyanidin accumulation in cabernet sauvignon berries: a multi-dimensional analysis integrating climate, soil, and microbiota - Qi He; Yizhao Ren; Jiayi Li; Wanzhi Li; Mingyuan Zheng; Bingbing Duan; Artak Gabrielyan; Chao Li; Meilong Xu; Xu Liu (Food Research International, 2026)

Phase diagram engineering advances the thermoelectric performance of Zintl phase EuZn2Sb2 - Baopeng Ma; Honghao Yao; Shanghao Chen; Xiaofang Li; Shiquan Lu; Wenhua Xue; Tianyu Zhang; Linmao Wen; Sichen Duan; Yunzi Ren; Yumei Wang; Feng Cao; et al. (Chemical Engineering Journal, 2026)

TEC2Ne: a physics-informed deep learning framework for reconstructing ionospheric electron density profiles from global TEC maps - Chenghao Li; Hanxian Fang; Chao Xiao; Die Duan; Yang Lin; Hongtao Huang; Ganming Ren; Han Wu; Chuyue Zhou; Haiyang Zheng; Xuhui Shen; Xiaoqun Cao (GPS Solutions, 2026)

Microplastics identification framework: Integration of microplastic-derived dissolved organic matter fingerprints and machine learning - Ruxin Yang; Jinjiang Duan; Jianhao Song; Linhu Li; Xingnian Ren; Cheng Yang; Yu Xiang; Han Zhang; Mengli Chen (Water Research, 2026)

Effects of host plants on the insecticide susceptibility of Spodoptera frugiperda - Yue Yuan; Yaqin Zou; Kaiyi Zeng; Wenyan Duan; Feiyue Ren; Liutong Ye; Jingjing Fang; Zhihong Xu; Xiaolei Zhang; Junkai Li (Journal of Pest Science, 2026)

Study on oxidative stress and nitric oxide response mechanisms in Gymnodinium sp. under polystyrene microplastic stress - Zhen Ren; Zheng–Xin Hu; Xue Deng; Pei–Feng Li; Chun–Ying Liu; Shan–Shan Duan; Xiang–Feng Kong; Gui–Peng Yang (Journal of Applied Phycology, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

In-situ upgrading of waste passenger car tires via molten salt thermal treatment: Effects of particle size and temperature - Yang Ren; Xinhong Yuan; Yang Hu; Hongyun Hu; Kai Jiang; Zhen Wu; Yongxin Duan; Xian Li; Hong Yao (Journal of Cleaner Production, 2026)

Two-step pyrolysis enabled by bentonite catalysis for the co-production of bioactive humic acid and functional carbon-clay composites - Huanhuan Li; Jiarun Duan; Lijuan Zhang; Yong Wen; Yun Xiang; Chen Qiu; Junmei An; Zhiguo Guo; Yidong Cai; Changchun Ge; Xiaona Ren; Xinjiang Zhou; et al. (Environmental Research, 2026)

Deciphering Er3+ energy level population in La2Sn2O7 nanocrystals via tailored short-range energy transfer for multidimensional applications - Jiamei Ren; Bin Duan; Kejie Li; Jiaqi Zhao; Dongxu Guo; Ruiying Lu; Tianqi Sheng; Zuoling Fu (Chemical Engineering Journal, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Geranic acid as a novel antimicrobial agent for controlling Aeromonas veronii in meat products - Yuyang Duan; Yitong Ren; Jiayao Peng; Yingying Hao; Fangfei Zhang; Yi Li (International Journal of Food Microbiology, 2026)

Engineering phage endolysins and receptor-binding proteins for foodborne pathogen control and detection: A review and AI-driven framework - Zongcheng Wu; Xiaofeng Yu; Honglin Ren; Chunyi Shangguan; Cheng Han; Xi Yang; Shuaihao Qi; Xuepeng Duan; Han Wang; Pan Hu; Yansong Li; Qiang Lu; et al. (International Journal of Food Microbiology, 2026)

Flavor deterioration and texture changes in mud-packing salted egg yolks: A role of lipid oxidation and fatty acid degradation - Mingcai Duan; Qiqi Li; Ligen Xu; Lizhi Lu; Jindong Ren; Ligen Zou; Zhaoxia Cai (Food Chemistry, 2026)

Investigation on the High Food Availability Zone in riparian areas: From the perspective of fish food supply - Xiangdong Pan; Shuang Ren; Jingjie Feng; Ran Li; Yi Duan; Xiaolong Cheng (Ecohydrology & Hydrobiology, 2026)

Non-invasive crab gender detection based on carapace features using image enhancement and BLC-YOLOv8n - Xin Li; Jiaxuan Yu; Daoliang Li; Ni Ren; Qingling Duan; Jing Jin (Aquaculture International, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

The shake table test study on high-rise shear wall group considering the variation of concrete mechanical properties - Jian-Bing Chen; Jia-Qing Duan; Xiao-Dan Ren; Jie Li (Engineering Structures, 2026)

From passive to bioactive: Engineering a smart Band-Aid for complex wound care - Bin Zhu; Xueling Yang; Haiting Ren; Sergio Martin- Saldaña; Wanglin Duan; Bo Zhang; Qingzu Liu; Luyao Feng; Ye Zhu; Yurong Chen; Lu Dang; Jinqing Li; et al. (Chemical Engineering Journal, 2026)

Research on scientific and technological applications of spaceborne GNSS for China’s Space Station - Yifan Duan; Xinyuan Mao; Xuzhi Li; Leizheng Shu; Xiaoyu Chen; Yong Zhang; Bingxian Luo; Tingling Ren; Jun Sun; Shushi Liu; Wenbin Wang; Yang Gao (Advances in Space Research, 2026)

Antifungal activity and action mechanism of thymol, a mycotoxin inhibitor, against Fusarium asiaticum - Jie Zhang; Fuhao Ren; Han Gao; Yige Li; Xiaoru Yin; Zehua Zhou; Ziyang Zhang; Hui Qiu; Yiqiang Cai; Larisa Shcherbakova; Vitaly Dzhavakhiya; Yabing Duan (Food Chemistry, 2026)

Structured wave-transparent metamaterials for simultaneous broadband electromagnetic and acoustic absorption - Tongtong Zhang; Qingxuan Liang; Yubing Duan; Xin Yan; Aoqi Ren; Jiaming Feng; Dichen Li (Chemical Engineering Journal, 2026)

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Carbon paper-based Fe-co-Mn cathode synergistically enhances electro-Fenton system for non-radical degradation of 2-mercaptobenzothiazole - Xiaoqiang Li; Xiaorui Zhang; Xin Zhang; Shengjun Wen; Xiaoxiao Duan; Yongsheng Ren (Chemical Engineering Journal, 2026)

H2-induced restructuring of Mn for highly dispersed Pt species on PtMn/S-1 toward enhanced propane dehydrogenation - Jiamin Liu; Caixin Zou; Lizhi Wu; Jun Zuo; Mengjia Zhu; Qiwei Duan; Zhuangzhuang Ren; Juncheng He; Yirong Wang; Yu Tang; Zhuoxi Zhuo; Li Tan (Chemical Engineering Journal, 2026)

Artificial Intelligence techniques in data assimilation: Emerging approaches, key challenges, and future prospects - Wuxin Wang; Weicheng Ni; Taikang Yuan; Lilan Huang; Tao Han; Boheng Duan; Xiaoyong Li; Yanlai Zhao; Ben Fei; Lei Bai; Kaijun Ren (Science China Earth Sciences, 2026)

Thermoelectric properties of iron-bearing minerals in typical sinter and pellets: formation mechanism and industrial applications - Bowen Duan; Xiuli Han; Jiahui Ren; Yuxin Xie; Xiaoyu Sun; Fengjiu Li (Minerals Engineering, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Numerical investigation on the diffusion combustion characteristics of hydrogen ignited by polyoxymethylene dimethyl ethers 3 (PODE3) and diesel - Huiquan Duan; Haoran Sun; Min Liu; Chongchong Ren; Guoxiang Li; Shuzhan Bai (Fuel, 2026)

Brazide: A breakthrough plant growth regulator that delays leaf senescence under heat stress to promote grain yield in winter wheat (Triticum aestivum L.) - Xingyu Zhong; Qihua Wu; Le Yang; Ziqing Lin; Dan Ren; Zhaohu Li; Yuyi Zhou; Liusheng Duan (Field Crops Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Tree-ring δ18O reveals thaw-buffered warming in northernmost permafrost regions of China - Jiachuan Wang; Qiang Li; Yang Xu; Zichun Jia; Yifan Wu; Changfeng Sun; Yanchao Wang; Zhenchuan Niu; Meng Ren; Qiufang Cai; Xiangyu Duan; Wentai Liu; et al. (Quaternary Science Reviews, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Indirect influence of the Siberian high on the increased annual temperature range in southern Northeast Asia since the late 19th century: Insights from tree-ring δ18O - Jiachuan Wang; Qiang Li; Yang Xu; Zichun Jia; Yifan Wu; Changfeng Sun; Yanchao Wang; Zhenchuan Niu; Huiming Song; Meng Ren; Qiufang Cai; Xiangyu Duan; et al. (Global and Planetary Change, 2026)

4E-based performance evaluation of a solar-assisted SOFC–CCHP system integrating zero-energy CO2 enrichment and cascade waste heat recovery - Yunxiu Ren; Ming Yang; Nan Zheng; Qiang Zhang; Zherui Ma; Wenjiang Zou; Shaolong Wang; Xingqi Ding; Qiushi Wang; Yimin Li; Liqiang Duan (Fuel, 2026)

Unveiling the mystery of baijiu blending based on flavoromics - Jiawen Duan; Dan Qin; Lu Gao; Fei He; Yize Zhang; Hehe Li; Jinyuan Sun; Fazheng Ren; Baoguo Sun (Food Research International, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Estimation of water quality in coastal aquaculture waters using the combination of machine learning and unmanned aerial vehicle multispectral imagery - Weiqiang Li; Min Ren; Haibo Zhang; Yue Duan; Daosheng Chen; Saiqiang Li; Mingshan Xu; Lihua Wang; Xiaodong Yang (Aquaculture, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Error analysis of a simulated Fe resonance wind temperature lidar using frequency-scanning method and three-frequency ratio method - Duanchao Liu; Hanxian Fang; Jintai Li; Die Duan; Chao Xiao; Hongtao Huang; Ganming Ren (Advances in Space Research, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Dual-model LSTM-Transformer framework with hydrodynamic adaptability for TN/TP predictions in tidal reaches - Zenghui Li; Xiaopeng Li; Zhihao Wang; Zihao Li; Peng Wang; Futian Ren; Qiannan Duan; Xiaowei Lu; Lei Huang (Journal of Hydrology, 2025)

Spatio-temporal variability of lacustrine groundwater discharge and related pollutant fluxes in an agricultural drainage lake: Coupled influence of meteorological factors and vegetation coverage dynamics - Yuanzhen Zhao; Shen Qu; Muhan Li; Limin Duan; Yiming Zhao; Xiaohui Ren; Xu Yang; Shaogang Dong; Ruihong Yu (Journal of Hydrology, 2025)

A new insight of size-dependent plastics particles kinetics with regarding of metabolomics effects in liver and kidney - Hongying Gao; Jing Li; Zehua Xu; Yiyang Duan; Bowen Su; Mengting Li; Banyun Zheng; Miaomiao Ren; Hao Chang; Heng Wang; Yi Lin; Heqing Shen (Environmental Pollution, 2025)

Effects of different straw returning amounts on soil physicochemical properties, dry matter accumulation, and yield of wheat - Shaokun Duan; Panpan Gai; Maofei Ren; Xiaohui Wang; Xumeng Li (Cereal Research Communications, 2025)
As a main way to reuse straw resources in the farmland, returning straw to the soil can effectively alleviate the adverse effects of direct straw burning on the soil and environment. Although there are previous studies on this aspect, few studies investigate the impact of the annual return of rice and wheat straws on wheat yield and soil properties. In this study, wheat ‘Annong 1124’ was used as the material. The four experimental treatments include: neither rice nor wheat straw returned to the field (R0), wheat straw returned to the field (RW), rice straw returned to the field (RR) and, both rice and wheat straw returned to the field (R2) were set up. The effects of different amounts of straw returning on soil physical and chemical properties, soil nutrient content, dry matter accumulation, and yield of wheat were studied, to clarify the characteristics of wheat yield formation, soil properties, and nutrient content changes under the condition of rice and wheat annual straw return. The results showed that straw returning increased soil aggregate content and root activity of wheat at the jointing stage. Still, they decreased soil pH and root activity at the flowering stage and increased soil aggregate content at small particle size ( d ≤ 0.5 mm and 0.50 mm < d ≤ 1.00 mm). Straw incorporation (R2, RR, and RW) decreased soil urease activity in the early growth stage, increased soil urease activity in the late wheat growth stage, and increased soil nutrient content. Straw returning improved the dry matter quantity of wheat at the jointing stage and had a great difference in the dry matter accumulation of wheat at the flowering stage. RR and R2 treatments reduced the dry matter accumulation of wheat at anthesis by 11.97% and 7.38%, respectively, while RW treatment increased the dry matter accumulation by 25.38%. Straw returning (RW, RR, and R2) decreased the number of wheat spikes but increased the number of grains per spike and 1000-grain weight. In 2019 and 2020, RW treatment increased wheat yield by 1.32% and 3.76%, RR and R2 treatment decreased wheat yield by 2.82%, 0.78%, and 1.70%, 0.42%, respectively. The results of path analysis showed that soil pH, soil biomass carbon, and soil urease activity had significant effects on wheat yield, especially soil biomass carbon. In summary, RW treatment increased soil nutrient content first and then increased dry matter accumulation at the flowering stage, which was beneficial to the transportation of dry matter from stem and leaf to grain. The grain number per spike and 1000-grain weight of wheat increased, but RR and R2 decreased the yield of wheat. Therefore, whether or not straw returning to the field can improve crop yield is related to the way straw returns to the field and crop type, as well as the time of straw returning.

Human-induced water-environment changes recorded in tree rings in the lower Tarim River - Xiangyu Duan; Yu Liu; Huiming Song; Meng Ren; Qiufang Cai; Changfeng Sun; Qiang Li; Hongbo Ling; Tongwen Zhang; Mao Ye; Nanjian Liu (Journal of Hydrology, 2025)

Integration of PMF and explainable machine learning for source apportionment and ecological risk of microplastics in urban greenspaces - Jianhao Song; Xingnian Ren; Jinjiang Duan; Kailei Li; Xiangbin Gao; Cheng Yang; Yu Xiang; Lei He; Han Zhang; Dongdong Gao; Ruxin Yang; Mengli Chen (Journal of Hazardous Materials, 2025)

Phylogenomic insights into historical biogeography and species delimitation of African Ampelocissus (Vitaceae) - Romer Narindra Rabarijaona; Jin-Ren Yu; Zhi-Yong Tang; Rindra Manasoa Ranaivoson; Russell L. Barrett; Mijoro Rakotoarinivo; Bing Liu; Yi-Chen You; Samaila S. Yaradua; Romeo Gbiribou; Jun Wen; Zhi-Duan Chen; et al. (Molecular Phylogenetics and Evolution, 2025)

Straw humification coefficient and its relation to soil carbon and nitrogen status - Yue Sun; Huiying Wang; Wei Jia; Keyu Ren; Bingjie Li; Hongqin Zou; Yinghua Duan; Minggang Xu (Journal of Environmental Management, 2025)

Innovative municipal sludge dewatering: High efficiency and high-dryness through the synergistic effect of MoS2 piezoelectric catalysis and electro-dewatering - Binqi Rao; Yulin Li; Zhuo Zeng; Yin Duan; Yan Zhang; Fang Zhou; Weilun Ren; Pin Zhou; Xilong Lu; Quanfa Zhou; Peng Xu (Journal of Environmental Management, 2025)

Exploration of shared diagnostic genes and mechanisms between crohn’s disease and ischemic stroke by integrated comprehensive bioinformatics analysis and machine learning - Chunlin Ren; Xinmin Li; Fangjie Yang; Jing Wang; Pengxue Guo; Zhenfei Duan; Yuting Kong; Mengyao Bi; Yongqi Yuan; Tian Tian; Yasu Zhang (Mammalian Genome, 2025)

Analysis of the seed filling performance influenced by maize seed shape, posture, and suction force - Zhaodong Li; Dinglin Ren; Jialuo Huang; Jiajie Wu; Delong Duan; Tian Zhang; Yongxin Chen (Biosystems Engineering, 2025)

Impact of long-term and short-term magnesium hydroxide dosing on transformation of chemical biomarkers in the sewer systems - Jiaying Li; Xiaotong Cen; Qiuda Zheng; Zeyang Zhao; Jianan Ren; Stuart Khan; Haoran Duan; Phong Thai; Min Zheng (Water Research, 2025)

Reprogramming Schizochytrium cell factory for High-Yield production of astaxanthin via mutagenesis and metabolic engineering - Yi Hu; Yu Duan; Yuan Zhang; Longxue Ma; Yida Zhai; Wuxi Chen; Liucheng Long; Wenqin Bai; Yanbing Shen; Limei Chen; Xiaoqing Ren; Demao Li (Chemical Engineering Journal, 2025)

Drought reconstructions over the past 552 years based on minimum earlywood density in central Tianshan Mountains - Yifan Ma; Huiming Song; Yu Liu; Quan Zhang; Meng Ren; Qiufang Cai; Tongwen Zhang; Kambiz Pourtahmasi; Xiangyu Duan; Pei Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Joint optimization of ship traffic organization and berth allocation in a seaport with one-way channel - Fuquan Xu; Hongxiang Ren; Yating Duan; Ye Li; Tianhui Zhu (Ocean Engineering, 2025)

Recent cooling enhances glacier resilience to global warming in the northern Karakoram: Evidence from tree rings - Wentai Liu; Qiang Li; Qiufang Cai; Huiming Song; Changfeng Sun; Piotr Owczarek; Meng Ren; Yifan Ma; Xiangyu Duan; Olga Solomina; Vladimir Matskovsky; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A half-century drying in Gobi Oasis, possible role of ENSO and warming/moistening of Northwest China - Qiang Li; Yifan Wu; Xiangyu Duan; Yu Liu; Changfeng Sun; Huiming Song; Qiufang Cai; Meng Ren; Jiachuan Wang; Zichun Jia; Hai Cheng (Global and Planetary Change, 2025)

High-performance, formaldehyde-free, multi-functional nitrocellulose adhesive in various environments - Xue Zhang; Yue Zhou; Zhaoqian Li; Juan Zhu; Junming Ren; Xikai Duan; Jinpeng Shen; Xiaohui Duan; Chonghua Pei (Chemical Engineering Journal, 2025)

Molecular biomarkers for the prognosis of breast cancer: role of amino acid metabolism genes - Yudong Zhou; Shibo Yu; Lizhe Zhu; Yalong Wang; Chenglong Duan; Danni Li; Jinsui Du; Jiaqi Zhang; Jianing Zhang; Ruichao Ma; Jianjun He; Yu Ren; et al. (Journal of Physiology and Biochemistry, 2025)
The development of precise molecular biomarkers for breast cancer prognosis holds immense potential to improve treatment outcomes. This study aimed to investigate the role of amino acid metabolism genes as predictive markers for breast cancer prognosis and their association with the immune-tumour microenvironment. By employing advanced machine learning algorithms and bioinformatics analysis techniques, the impact of amino acid metabolism-related genes (AAMRGs) on the immune status and overall survival of patients with breast cancer was examined. An AAMRG-based risk model was established to assess the prognostic significance. Validated risk models (AIMP2, IYD, and QARS1) accurately predicted patient outcomes [1 y: 0.87 (0.96–0.78); 3 y: 0.82 (0.87–0.76); 5 y: 0.80 (0.86–0.75)]. Furthermore, this study revealed evidence suggesting that QARS1 may influence breast cancer cell proliferation through methionine metabolism. This analysis provides valuable insights into the mechanisms of breast cancer, emphasizing the significance of AAMRGs as prognostic biomarkers and potential therapeutic targets for optimizing personalized treatment strategies.

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Investigation into the reaction mechanism for enhanced peracetic acid catalytic decomposition by coexisting hydrogen peroxide under electrochemical conditions - Siqi Chen; Zhen Liu; Mengyu Li; Bangxing Ren; Rong Liu; Chuanliang Zhao; Yuhang Liu; Zhe Zhang; Xiaodi Duan; Yao Chen (Process Safety and Environmental Protection, 2025)

The NiO hole transport layer between BiVO4 and Ni5P4 for photoelectrochemical water oxidation to hydrogen peroxide - Kai Cheng; Junyu Ren; Jingkun Wang; Naik Muhammad; Yupeng Chen; Fangzhou Zhou; Junjie Guo; Dong Duan; Tianbao Li; Bingshe Xu (Chemical Engineering Journal, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Activated CdS/ sulfur doped g-C3N4 photocatalyst for dye and antibiotic degradation: Experimental and DFT verification of S-scheme heterojunction - Xu Duan; Jian Yang; Jiaqing Zhu; Hongbin Li; Yujie Fang; Runxue Liu; Chen Yang; Weizao Liu; Chunlian Ding; Qingcai Liu; Jiangling Li; Shan Ren (Environmental Research, 2025)

Investigation on the influence mechanism of N element doping on the photocatalytic properties of the g-C3N4@ZnCdS composite photocatalyst - Fucheng Yu; Ruobing Jiang; Xuying Duan; Jielin Zhang; Jinlong Ren; Chenchen Feng; Cuixia Li; Kechao Hu; Xiaogang Hou (Journal of Water Process Engineering, 2025)

Spatio-temporal coupling coordination analysis between local governments' environmental performance and listed companies' ESG performance - Xia Wu; Chunxu Hao; Yuhan Li; Chazhong Ge; Xianming Duan; Jing Ren; Cong Han (Environmental Impact Assessment Review, 2025)

Novel and efficient techniques in the discovery of antioxidant peptides - Yuhao Zhang; Yun Li; Tianyi Ren; Ping Xiao; Jin-ao Duan (Critical Reviews in Food Science and Nutrition, 2024)

Resistance risk and mechanism of Ustilaginoidea virens to pydiflumetofen - Xiaoru Yin; Xinlong Gao; Xin Shen; Fuhao Ren; Yige Li; Mingguo Zhou; Jie Zhang; Yabing Duan (Pesticide Biochemistry and Physiology, 2024)

Chain effect of Mn4+/ Mn3+ and OLattice on La1-xSrxMnO3 catalysts for lower thermally driven CO oxidation - Xu Duan; Jian Yang; Jiaqing Zhu; Hongbin Li; Huan Li; Runxue Liu; Yujie Fang; Qingcai Liu; Weizao Liu; Chunlian Ding; Jiangling Li; Shan Ren (Journal of Environmental Chemical Engineering, 2024)

Electrochemically enhanced hydrophobic modification of La-doped PbO2 anode by peroxymonosulfate for ceftazidime removal - Xiaoqiang Li; Jian Wang; Xiaoxiao Duan; Yongsheng Ren (Journal of Environmental Chemical Engineering, 2024)

The hepatoprotective effect of sodium butyrate on hepatic inflammatory injury mediated by the NLRP3 inflammatory pathway in subchronic fluoride-exposed mice - Wen Li; Zhiyu Ma; Cuijing Su; Funing Liu; Nan Yan; Xiaoxu Duan; Zhenxiang Sun; Hongbo Wang; Yufei Ma; Zhengdong Wang; Fu Ren (Molecular Biology Reports, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

SAP130 mediates crosstalk between hepatocyte ferroptosis and M1 macrophage polarization in PFOS-induced hepatotoxicity - Longfei Li; Jingyi Ren; Mingmei Guo; Ziwen An; Wenjing Duan; Junli Lv; Zhenzhen Tan; Jing Yang; Yiming Zhu; Huiling Yang; Yi Liu; Yuxia Ma; et al. (Science of The Total Environment, 2024)

Western Mongolian Plateau exhibits increasing Holocene temperature - Chong Huang; Xiaozhong Huang; Jinbao Li; Ling Wang; Lan Jiang; Lixiong Xiang; Jun Zhang; Yu Hu; Xiaoyan Mu; Min Zheng; Xiuxiu Ren; Tao Wang; et al. (Global and Planetary Change, 2024)

Source-specific probabilistic health risk assessment of dust PAHs in urban parks based on positive matrix factorization and Monte Carlo simulation - Haijing Duan; Yanfeng Wang; Haoxin Shen; Chong Ren; Jing Li; Jiaheng Li; Yangyang Wang; Yanxia Su (Environmental Geochemistry and Health, 2024)

Autophagy activation ameliorates the fibrosis of trabecular meshwork cells induced by TGFβ2 through the promotion of fibrotic proteins degradation - Gang Wang; Rumeng Zhao; Zhenyang Guo; Huiling Cui; Di Wang; Jing Ren; Shichao Zhu; Ke Zhang; Bo Tang; Jingyi Zhang; Peng Li; Shichao Duan; et al. (Human Cell, 2024)

Electrochemical degradation of m-nitrophenol using an innovative zeolite modified PbO2 anode: Electrode characterization, influence factors and degradation mechanism - Xiaoyue Duan; Yitong Li; Xinyu Sui; Xuesong Zhao; Xin Ren; Limin Chang (Journal of Environmental Chemical Engineering, 2024)

High sensitive detection of Cd, Hg, Pb and Cr in rice based on LA-MPT-OES with optimized excitation regions by two-dimensional characterization of plasma plume - Lingwei Zeng; Yu Rao; Weiheng Kong; Mengfan Wu; Wenxin Ren; Shijie Li; Jianxiong Dai; Yixiang Duan (Food Chemistry, 2024)

Silica nanoparticles induce liver lipid metabolism disorder via ACSL4-mediated ferroptosis - Mengqi Sun; Qinglin Sun; Tianyu Li; Xiaoke Ren; Qing Xu; Zhiwei Sun; Junchao Duan (Environmental Pollution, 2024)

Amino polycarboxylic acid complex agent modified Fe0 enhanced activation of H2O2 double decomposition pathways for tetracycline removal under neutral condition - Zhujun Dong; Zhutong Dong; Yuzhu Xue; Haiying Lu; Minyi Yu; Yao Duan; Xiaoyu Li; Zihao Li; Wenyan Zhang; Gengbo Ren; Chen Chen; Xiang Li; et al. (Chemical Engineering Journal, 2024)

Deciphering physiological and transcriptional mechanisms of maize seed germination - Yaqi Jie; Wei Wang; Zishan Wu; Zhaobin Ren; Lu Li; Yuyi Zhou; Mingcai Zhang; Zhaohu Li; Fei Yi; Liusheng Duan (Plant Molecular Biology, 2024)

Targeting selective inhibitors of PARPs in drug discovery and development - Maolin Duan; Jing Gao; Jiajin Li; Xiaoli Huang; Yijiu Ren; Yang Li; Mengya Liao; Yiwen Zhang (Medicinal Chemistry Research, 2024)

A combined extended triple collocation and cumulative distribution function merging framework for improved daily precipitation estimates over mainland China - Linyong Wei; Shanhu Jiang; Jianzhi Dong; Liliang Ren; Bin Yong; Bang Yang; Xueying Li; Zheng Duan (Journal of Hydrology, 2024)

Aspirin exposure coupled with hypoxia interferes energy metabolism, antioxidant and autophagic processes and causes liver injury in estuarine goby Mugilogobius chulae - Yimeng Wang; Yufei Zhao; Weibo Gong; Yingshi Hou; Jinzhi Ren; Chunni Duan; Huiyu Zhang; Xiangping Nie; Jianjun Li (Journal of Hazardous Materials, 2024)

MJO-equatorial Rossby wave interferences in the tropical intraseasonal oscillation - Yuntao Wei; Hong-Li Ren; Wansuo Duan; Guodong Sun (Climate Dynamics, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Ash melting behaviors of high-sodium coal and its co-combustion with coal gangue to inhibit slagging - Li Zhang; Duan Ke; Jingchong Yan; Zhiping Lei; Zhanku Li; Weidong Zhang; Shigang Kang; Zhicai Wang; Shibiao Ren; Hengfu Shui (Fuel, 2024)

Empagliflozin rescues lifespan and liver senescence in naturally aged mice - Jiangchuan Long; Ziyu Ren; Yaqian Duan; Wei Tao; Xi Li; Shengbing Li; Ke Li; Qixuan Huang; Jie Chen; Mengliu Yang; Yang Li; Xie Luo; et al. (GeroScience, 2024)

Atorvastatin causes developmental and behavioral toxicity in yellowstripe goby (Mugilogobius chulae) embryos/larvae via disrupting lipid metabolism and autophagy processes - Yufei Zhao; Yimeng Wang; Jinzhi Ren; Weibo Gong; Xiangping Nie; Ying Peng; Jianjun Li; Chunni Duan (Aquatic Toxicology, 2024)

Biomechanical properties of articular cartilage in different regions and sites of the knee joint: acquisition of osteochondral allografts - Yongsheng Ma; Qitai Lin; Xueding Wang; Yang Liu; Xiangyang Yu; Zhiyuan Ren; Yuanyu Zhang; Li Guo; Xiaogang Wu; Xiangyu Zhang; Pengcui Li; Wangping Duan; et al. (Cell and Tissue Banking, 2024)
Osteochondral allograft (OCA) transplantation involves grafting of natural hyaline cartilage and supporting subchondral bone into the cartilage defect area to restore its biomechanical and tissue structure. However, differences in biomechanical properties and donor-host matching may impair the integration of articular cartilage (AC). This study analyzed the biomechanical properties of the AC in different regions of different sites of the knee joint and provided a novel approach to OCA transplantation. Intact stifle joints from skeletally mature pigs were collected from a local abattoir less than 8 h after slaughter. OCAs were collected from different regions of the joints. The patella and the tibial plateau were divided into medial and lateral regions, while the trochlea and femoral condyle were divided into six regions. The OCAs were analyzed and compared for Young’s modulus, the compressive modulus, and cartilage thickness. Young’s modulus, cartilage thickness, and compressive modulus of OCA were significantly different in different regions of the joints. A negative correlation was observed between Young's modulus and the proportion of the subchondral bone (r = − 0.4241, P < 0.0001). Cartilage thickness was positively correlated with Young’s modulus (r = 0.4473, P < 0.0001) and the compressive modulus (r = 0.3678, P < 0.0001). During OCA transplantation, OCAs should be transplanted in the same regions, or at the closest possible regions to maintain consistency of the biomechanical properties and cartilage thickness of the donor and recipient, to ensure smooth integration with the surrounding tissue. A 7 mm depth achieved a higher Young's modulus, and may represent the ideal length.

Structure-activity relationship and mechanistic study of organotins as inhibitors of human, pig, and rat gonadal 3β-hydroxysteroid dehydrogenases - Peiyu Wang; Zhongyao Ji; Huiqian Chen; Sailing Chen; Chengshuang Pan; Qianjin Fei; Ren-shan Ge; Ping Duan; Linxi Li (Toxicology and Applied Pharmacology, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Role of surface species in CO oxidation over CuO@LaMnO3 nanocomposites: Effect of calcination temperature - Huan Li; Jian Yang; Yujie Fang; Xu Duan; Chen Yang; Shuangshuang Liu; Weizao Liu; Qingcai Liu; Shan Ren (Journal of Environmental Chemical Engineering, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Ionic liquid for selective extraction of lithium ions from Tibetan salt lake brine with high Na/Li ratio - Rujie Li; Yangyang Wang; Linli Chen; Wenjing Duan; Zhongqi Ren; Zhiyong Zhou (Desalination, 2024)

Numerical simulation analysis of debris filtration in the bottom nozzle - Shuang Deng; Quan-yao Ren; Jing Zhang; Xin Duan; Fa-wen Zhu; Yong Xin; Xin-Yu Yang; Quan Li; Ying-wei Wu (Annals of Nuclear Energy, 2024)

Regulating pathway for bacterial diversities toward improved ecological benefits of thiencarbazone-methyl·isoxaflutole application: A field experiment - Yonglu Wang; Liyun Zhang; Shumin Zhang; Shiliang Zhu; Fengsong Zhang; Guixiang Zhang; Bihua Duan; Rui Ren; Hongyu Zhang; Meng Han; Yi Xu; Yuyang Li (Journal of Environmental Management, 2024)

Response of lipid metabolism, energy supply, and cell fate in yellowstripe goby (Mugilogobius chulae) exposed to environmentally relevant concentrations atorvastatin - Yufei Zhao; Chunni Duan; Huiyu Zhang; Weibo Gong; Yimeng Wang; Jinzhi Ren; Xiangping Nie; Jianjun Li (Environmental Pollution, 2024)

Global, regional, and national burden of asbestosis from 1990 to 2019 and the implications for prevention and control - Zejin Ou; Xin Li; Jiaxin Cui; Shaofang Zhu; Kexin Feng; Jialao Ma; Kangyong Wu; Yuquan Chen; Yiwei Su; Shihao Tang; Danping Duan; Yixian Ren; et al. (Science of The Total Environment, 2023)

Associations of long-term particulate matter exposure with cardiometabolic diseases: A systematic review and meta-analysis - Mengqi Sun; Tianyu Li; Qinglin Sun; Xiaoke Ren; Zhiwei Sun; Junchao Duan (Science of The Total Environment, 2023)

Thermodynamic mechanism insights into the dynamic evolution of nanofiltration membrane fouling: Effect of calcium ion on organic fouling - Yunhuan Chen; Rui Zhang; Guanxiao Wu; Jiapeng Li; Yongsheng Ren; Xiaoxiao Duan (Desalination, 2023)

Red Emission Carbon Nanoparticles Which Can Simultaneously Responding to Hypochlorite and pH - Yinghua Liu; Wenxiu Duan; Huiqing Li; Jiang Wu; Dan Liu; Jiaying Mi; Shengda Qi; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Investigation on nanofiltration membrane fouling behaviour of cation-induced apam in strontium-bearing mine water - Siao Zhao; Yunhuan Chen; Guanxiao Wu; Jiapeng Li; Yongsheng Ren; Xiaoxiao Duan (Journal of Environmental Chemical Engineering, 2023)

Correction to: Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2023)

Tartary buckwheat root polysaccharides ameliorate non-alcoholic fatty liver disease via the IL6-SOCS3-SREBP1c pathway - Litao Zhang; Shuo Wang; Yimin Li; Boyu Liu; Zeyu Duan; Fei Liu; Qiang Ren (Food and Chemical Toxicology, 2023)

Quantitative detection of naphthenic acids in wastewater based on superior fluorescence performance of nitrogen-rich carbon quantum dots - Yize Liu; Meiyu Li; Ruoyao Zhang; Tengda Zhao; Jing Han; Aibin Kang; Chunmao Chen; Hongwei Ren; Erhong Duan (Science of The Total Environment, 2023)

MitoQ ameliorates PM2.5-induced pulmonary fibrosis through regulating the mitochondria DNA homeostasis - Yang Li; Zhou Du; Tianyu Li; Xiaoke Ren; Yang Yu; Junchao Duan; Zhiwei Sun (Chemosphere, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Exogenous spraying of 4-chlorophenoxyacetic acid sodium salt promotes growth and flavonoid biosynthesis of mulberry leaves (Morus alba L.) - Zhen Zhang; Yun Duan; Yu Zhang; Shanying Zhang; Xiaoyu Liang; Jiahao Li; Saihao Ren; Chenghui Zhang; Meng Wang (Physiology and Molecular Biology of Plants, 2023)

Distinguishing Patients with MRI-Negative Temporal Lobe Epilepsy from Normal Controls Based on Individual Morphological Brain Network - Wenxiu Zhang; Ying Duan; Lei Qi; Zhimei Li; Jiechuan Ren; Naluyele Nangale; Chunlan Yang (Brain Topography, 2023)

Differences in the Default Mode Network of Temporal Lobe Epilepsy Patients Detected by Hilbert-Huang Transform Based Dynamic Functional Connectivity - Ye Yuan; Ying Duan; Wan Li; Jiechuan Ren; Zhimei Li; Chunlan Yang (Brain Topography, 2023)

Constructing C–O bridged CeO2/g-C3N4 S-scheme heterojunction for methyl orange photodegradation：Experimental and theoretical calculation - Chen Yang; Jian Yang; Shuangshuang Liu; Mingxue Zhao; Xu Duan; Hongli Wu; Lang Liu; Weizao Liu; Jiangling Li; Shan Ren; Qingcai Liu (Journal of Environmental Management, 2023)

Selective extraction of lithium ions from salt lake brines using a tributyl phosphate-sodium tetraphenyl boron-phenethyl isobutyrate system - Rujie Li; Yangyang Wang; Wenjing Duan; Chencan Du; Shichao Tian; Zhongqi Ren; Zhiyong Zhou (Desalination, 2023)

Norgestrel causes digestive gland injury in the clam Mactra veneriformis: An integrated histological, transcriptomics, and metabolomics study - Xiaoran Zhao; Qing Wang; Xiangfei Li; Hua Xu; Chuanbo Ren; Yanyan Yang; Shuhao Xu; Guoxing Wei; Yujun Duan; Zhitao Tan; Yan Fang (Science of The Total Environment, 2023)

Interactions of co-firing coal gangue and high sodium coal: Combustion characteristics and emission behaviors of polluting gases - Duan Ke; Li Zhang; Jingchong Yan; Zhao Lei; Zhiping Lei; Zhanku Li; Shibiao Ren; Zhicai Wang; Hengfu Shui (Fuel, 2023)

Freshwater crustacean exposed to active pharmaceutical ingredients: ecotoxicological effects and mechanisms - Jiahua Guo; Jingya Ren; Chao Chang; Qiannan Duan; Jun Li; Mirella Kanerva; Fangshe Yang; Jiezhang Mo (Environmental Science and Pollution Research, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Magnesium Hydroxide Slurry Coagulation-Adsorption Performance for Reactive Orange Removal Assisted with PAM - Xiaoli Deng; Jianhai Zhao; Xiuming Qiu; Yingying Duan; Xiaoyu Ren; Wenpu Li; Rong Mu; Hongying Yuan (Water, Air, & Soil Pollution, 2023)

Fitness consequences of oviposition choice by an herbivorous insect on a host plant colonized by an endophytic entomopathogenic fungus - Hui Zhu; Jun Fu; Han Wang; Michael J. Bidochka; Mingyi Duan; Wenjing Xu; Li Sui; Bingzhong Ren; Qiyun Li; Zhengkun Zhang (Journal of Pest Science, 2023)

One-step synthesis of heteropolyacid ionic liquid as co-extraction agent for recovery of lithium from aqueous solution with high magnesium/lithium ratio - Yangyang Wang; Wenjing Duan; Rujie Li; Fan Zhang; Shichao Tian; Zhongqi Ren; Zhiyong Zhou (Desalination, 2023)

Does climate policy uncertainty really affect corporate financialization? - Xiaohang Ren; Weichen Li; Kun Duan; Xinru Zhang (Environment, Development and Sustainability, 2023)

Pathological α-synuclein accumulation, CSF metabolites changes and brain microstructures in cynomolgus monkeys treated with 6-hydroxydopamine - Xue Gan; Jiahan Ren; Tianzhuang Huang; Kunhua Wu; Shulin Li; Yanchao Duan; Zhengbo Wang; Wei Si; Jingkuan Wei (NeuroToxicology, 2023)

CO2 mineral sequestration and nickel recovery from laterite ore by using waste copperas - Yuxiang Gao; Xi Jin; Liumei Teng; Sohrab Rohani; Minyu He; Jiangling Li; Shan Ren; Qingcai Liu; Junbin Huang; Huamei Duan; Yuntao Xin; Weizao Liu (Fuel, 2023)

Transforming growth factor-β signaling: From tissue fibrosis to therapeutic opportunities - Li-Li Ren; Xiao-Jun Li; Ting-Ting Duan; Zheng-Hai Li; Jun-Zheng Yang; Ya-Mei Zhang; Liang Zou; Hua Miao; Ying-Yong Zhao (Chemico-Biological Interactions, 2023)

A comprehensive comparison of data fusion approaches to multi-source precipitation observations: a case study in Sichuan province, China - Zhe Duan; Yufeng Ren; Xing Liu; Huike Lei; Xiaojun Hua; Xiaolong Shu; Li Zhou (Environmental Monitoring and Assessment, 2022)

Ginsenoside Rg1 Reduced Microglial Activation and Mitochondrial Dysfunction to Alleviate Depression-Like Behaviour Via the GAS5/EZH2/SOCS3/NRF2 Axis - Junnan Li; Wei Gao; Zhonghui Zhao; Yannan Li; Lixuan Yang; Wei Wei; Feifei Ren; Yang Li; Yao Yu; Wenzhe Duan; Jingchun Li; Baoan Dai; et al. (Molecular Neurobiology, 2022)
Ginsenoside Rg1 is the principal active ingredient in ginseng. The antidepressant effects of Rg1 have been validated; however, the specific underlying mechanism of this effect needs further research. Rats were subjected to the chronic restraint stress (CRS) depression model. Rg1, or a positive control drug, was administered to the rats. Depression-like behaviours were evaluated through behavioural experiments. Cytokine, mRNA, protein, ATP, and mitochondria DNA levels were detected using the indicated methods. Lentivirus-packaged plasmids were injected into the rat brain for GAS5 overexpression or knockdown. In vitro mitochondrial dysfunction was evaluated by detecting mitochondrial reactive oxygen species and mitochondrial membrane potential. Direct interaction between GAS5 and EZH2 was validated by RNA immunoprecipitation and RNA pull-down assay. The enrichment of EZH2 and H3K27me3 was evaluated through chromatin immunoprecipitation quantitative real-time PCR. Rg1 treatment alleviated depression-like behaviours, microglial activation, and mitochondrial dysfunction in CRS rats. Similarly, GAS5 knockdown revealed a similar protective effect of Rg1 treatment. GAS5 overexpression in the rat brain compromised the protective effect of Rg1 treatment. Moreover, Rg1 treatment or GAS5 knockdown attenuated microglial activation and mitochondrial dysfunction in vitro. Mechanically, GAS5 was suppressed SOCS3 and NRF2 expression by facilitating EZH2-mediated transcriptional repression. Rg1 attenuated microglial activation and improved mitochondrial dysfunction in depression by downregulating GAS5 expression. Mechanically, GAS5 might regulate microglial activation and mitochondrial dysfunction via the epigenetic suppression of NRF2 and SOCS3.

Effect of GLP-1R rs2254336 and rs3765467 polymorphisms on gastrointestinal adverse reactions in type 2 diabetes patients treated with liraglutide - Jiangchuan Long; Yongjian Liu; Yaqian Duan; Yang Li; Gangyi Yang; Ziyu Ren; Wei Tao; Dongfang Liu (European Journal of Clinical Pharmacology, 2022)

Stepwise‐clustered heatwave downscaling and projection for Guangdong Province - Jiayan Ren; Guohe Huang; Yongping Li; Xiong Zhou; Chen Lu; Ruixin Duan (International Journal of Climatology, 2022)
Heatwave events over Guangdong have attracted recent attention under changing climate conditions. It is desired to explore the future changes of heatwave due to its associated consequences on society economy and environment. In this study, a stepwise‐clustered heatwave downscaling approach (i.e., SCHW) was developed for the projection of HWs in Guangdong. The heatwave indicators (occurrence, duration, magnitude, intensity, frequency, and accumulated intensity) were investigated from both the absolute and relative definitions of heatwave events (i.e., AHWs and RHWs) based on the multi‐model ensemble of 13 coupled model intercomparison projected phase 5 (CMIP5) global climate models (GCMs) under two representative concentration pathways (RCPs). The trends (i.e., 0.18–0.29°C per decade under RCP4.5 and 0.30–0.58°C per decade under RCP8.5) of the projected daily maximum temperature indicate that Guangdong would experience continuous warming in the future. The occurrence, frequency, and accumulated intensity of heatwave would increase by 198%, 272%, and 346% in the 2080s (i.e., 2066–2095) under RCP8.5 compared to the historical period (i.e., 1976–2005), respectively. Moreover, the three indicators of HWs are projected to have more substantial increases over inland Guangdong than its costal parts. The spatial variation of occurrence of absolute and relative heatwave under RCP8.5 (2.80 and 2.78) is larger than these under RCP4.5 (2.50 and 2.32) during 2080s (i.e., 2066–2095). The projections of future HWs can help provide valuable information for assessing extreme climate change and identifying desired adaptation strategies.

Crude oil price uncertainty and corporate carbon emissions - Ping Wei; Yiying Li; Xiaohang Ren; Kun Duan (Environmental Science and Pollution Research, 2022)

Risk factors for sleep disorders in patients undergoing peritoneal dialysis - Gui-Ling Liu; Qiu-Nan Zhan; You-Lu Zhao; Zu-Ying Xiong; Jin-Lan Liao; Ye-Ping Ren; Qin Wang; Li-Ping Duan; Zhao-Xia Zheng; Li Hao; Jie Dong (Sleep and Biological Rhythms, 2021)
Sleep disorders in patients with end-stage renal disease are common but have rarely been reported in previous studies. Therefore, we examined the prevalence of sleep disorders and the risk factors for declining sleep quality in patients undergoing peritoneal dialysis (PD). A multicenter prospective cohort study was conducted at five PD centers across different provinces in China. A total of 449 patients who underwent PD between March to November 2013 were enrolled. Demographic data, laboratory indicators, presence of depression, and sleep assessment data were collected. Sleep questionnaires reflecting five categories of sleep disorders, namely, insomnia, restless legs syndrome, excessive daytime sleepiness, possible narcolepsy, and sleepwalking and nightmares, were administered at baseline and at 24 months postoperatively. Sleep disorders were diagnosed when a patient had at least one sleep problem. At baseline, 335 (74.6%) patients had at least one type of sleep disorder. Depression, diabetes mellitus (DM), and male were found to be associated with the presence of a sleep disorder. At follow-up, the prevalence of insomnia, restless legs syndrome, and excessive daytime sleepiness had significantly increased in 285 patients. Furthermore, cardiovascular disease (CVD) was found to be associated with the presence of sleep disorders in patients with one or more disorders at baseline, whereas a low serum albumin level was found to be associated with sleep disorders in patients without any sleep disorders at baseline. The prevalence of sleep disorders was relatively high among PD patients at baseline and increased afterthe2-year follow-up. Depression, DM, and male were associated with all sleep disorders at baseline. CVD was associated with the presence of a sleep disorder at baseline and worse sleep quality at the 2-year follow-up; whereas a low serum albumin level was associated with the risk of acquiring a sleep disorder at the 2-year follow-up among patients with normal sleep status at baseline.

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

A pair of new neo -clerodane diterpenoid epimers from the roots of Croton crassifolius and their anti-inflammatory - Dong-Bo Zhang; Zhi-Shu Tang; Pei Xie; Yan-Ni Liang; Jin-Gao Yu; Zhen Zhang; Dong-Zhu Duan; Chun-Li Cui; Zhong-Xing Song; Li Ren; Zheng Wang; Dao-Geng Yu (Natural Product Research, 2020)

Arsenic Distribution, Accumulation and Tolerance Mechanisms of Typha angustifolia in Different Phenological Growth Stages - Guiying Yang; Huan Zhong; Xue Liu; Chang’e Liu; Shiyu Li; Lei Hou; Yungen Liu; Yan Wang; Wei Ren; Changqun Duan (Bulletin of Environmental Contamination and Toxicology, 2020)

Event-based extreme precipitation in Central-Eastern China: large-scale anomalies and teleconnections - Wei Shang; Shuangshuang Li; Xuejuan Ren; Keqin Duan (Climate Dynamics, 2020)

Recovery of the non-functional EGFP-assisted identification of mutants generated by CRISPR/Cas9 - Chong Ren; Yuchen Guo; Elias Kirabi Gathunga; Wei Duan; Shaohua Li; Zhenchang Liang (Plant Cell Reports, 2019)

Characterization of the complete chloroplast genome of Cephalotaxus sinensis (Cupressales: Taxaceae), an endangered Tertiary relict tree endemic to China - Ren-Yan Duan; Li-Min Yang; Gan-Lin Wu (Conservation Genetics Resources, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Impacts of Land-Use Data on the Simulation of Surface Air Temperature in Northwest China - Yaohui Li; Cailing Zhao; Tiejun Zhang; Wei Wang; Haixia Duan; Yuanpu Liu; Yulong Ren; Zhaoxia Pu (Journal of Meteorological Research, 2018)

Effects of cadmium exposure on expression of glutathione synthetase system genes in Acidithiobacillus ferrooxidans - Chunli Zheng; Li Zhang; Minjie Chen; Xue Qiang Zhao; Yizhuo Duan; Ye Meng; Xuefeng Zhang; Ren Fang Shen (Extremophiles, 2018)

Effects of Updated RegCM4 Land Use Data on Near-Surface Temperature Simulation in China - Yulong Ren; Yaohui Li; Zhaoxia Pu; Tiejun Zhang; Haixia Duan; Wei Wang (Journal of Meteorological Research, 2018)

Relationship Between Fine-Particle Pollution and the Urban Heat Island in Beijing, China: Observational Evidence - Zuofang Zheng; Guoyu Ren; Hong Wang; Junxia Dou; Zhiqiu Gao; Chunfeng Duan; Yubin Li; Jean Paul Ngarukiyimana; Chun Zhao; Chang Cao; Mei Jiang; Yuanjian Yang (Boundary-Layer Meteorology, 2018)

Silica nanoparticle exposure inducing granulosa cell apoptosis and follicular atresia in female Balb/c mice - Jianhui Liu; Man Yang; Li Jing; Lihua Ren; Jialiu Wei; Jin Zhang; Feng Zhang; Junchao Duan; Xianqing Zhou; Zhiwei Sun (Environmental Science and Pollution Research, 2018)

Peroxisome proliferator-activated receptor alpha mediates C/EBP homologous protein to protect mice from acute liver failure - Xiangying Zhang; Peiling Dong; Hongbo Shi; Huaying Sun; Jianhui Lin; Dexi Chen; Zhongping Duan; Xiuhui Li; Feng Ren (Inflammation Research, 2017)

Characterization of the complete chloroplast genome of Emmenopterys henryi (Gentianales: Rubiaceae), an endangered relict tree species endemic to China - Ren-yan Duan; Min-yi Huang; Li-min Yang; Zhao-wen Liu (Conservation Genetics Resources, 2017)

New neolignan glycoside from the root of Aralia echinocaulis Hand. -Mazz - Yunzhi Li; Hui Cheng; Ren Yue; Mengmeng Duan; Mingdong Liu (Natural Product Research, 2017)

The complete chloroplast genome sequence of Pinus dabeshanensis - Ren-Yan Duan; Li-Min Yang; Tong Lv; Gan-Lin Wu; Min-Yi Huang (Conservation Genetics Resources, 2016)

Mineralization time and tectonic setting of the Zhengguang Au deposit in the Duobaoshan ore field, Heilongjiang Province, NE China - Yu-Jie Hao; Yun-Sheng Ren; Ming-Xin Duan; Xuan Zhao; Qun Yang; Kuang-Yin Tong; Chao Li (Arabian Journal of Geosciences, 2016)

Overexpression of the Monodehydroascorbate Reductase Gene from Non-heading Chinese Cabbage Reduces Ascorbate Level and Growth in Transgenic Tobacco - Jun Ren; Weike Duan; Zhongwen Chen; Shuo Zhang; Xiaoming Song; Tongkun Liu; Xilin Hou; Ying Li (Plant Molecular Biology Reporter, 2015)

Molecular cloning and expression analysis of Relish gene from the ridgetail white prawn Exopalaemon carinicauda - Qianqian Ge; Junping Liang; Jitao Li; Jian Li; Yafei Duan; Fazhen Zhao; Hai Ren (Fisheries Science, 2015)

Genome-wide analysis of the MADS-box gene family in Brassica rapa (Chinese cabbage) - Weike Duan; Xiaoming Song; Tongkun Liu; Zhinan Huang; Jun Ren; Xilin Hou; Ying Li (Molecular Genetics and Genomics, 2015)

Elevated plasma sphingomyelin (d18:1/22:0) is closely related to hepatic steatosis in patients with chronic hepatitis C virus infection - J.-F. Li; F. Qu; S.-J. Zheng; H.-L. Wu; M. Liu; S. Liu; Y. Ren; F. Ren; Y. Chen; Z.-P. Duan; J.-L. Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Genome-wide identification, classification and expression analysis of the heat shock transcription factor family in Chinese cabbage - Xiaoming Song; Gaofeng Liu; Weike Duan; Tongkun Liu; Zhinan Huang; Jun Ren; Ying Li; Xilin Hou (Molecular Genetics and Genomics, 2014)

The Role of ABA in the Maturation and Postharvest Life of a Nonclimacteric Sweet Cherry Fruit - Hao Luo; ShengJie Dai; Jie Ren; CaiXia Zhang; Ying Ding; Zhuang Li; Yufei Sun; Kai Ji; Yanping Wang; Qian Li; Pei Chen; Chaorui Duan; et al. (Journal of Plant Growth Regulation, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

The Proform of Glia Cell Line-Derived Neurotrophic Factor: a Potentially Biologically Active Protein - Xiao-Long Sun; Bei-Yu Chen; Li Duan; Yi Xia; Zhuo-Jing Luo; Jing-Jie Wang; Zhi-Ren Rao; Liang-Wei Chen (Molecular Neurobiology, 2014)

Regurgitant Derived From the Tea Geometrid Ectropis obliqua Suppresses Wound-Induced Polyphenol Oxidases Activity in Tea Plants - Zi-Wei Yang; Xiao-Na Duan; Shan Jin; Xi-Wang Li; Zong-Mao Chen; Bing-Zhong Ren; Xiao-Ling Sun (Journal of Chemical Ecology, 2013)

Nitrate or NaCl regulates floral induction in Arabidopsis thaliana - Tongkun Liu; Ying Li; Jun Ren; Yu Qian; Xuedong Yang; Weike Duan; Xilin Hou (Biologia, 2013)

Differential regulation of IGF-I and IGF-II gene expression in skeletal muscle cells - Shuang Jiao; Hongxia Ren; Yun Li; Jianfeng Zhou; Cunming Duan; Ling Lu (Molecular and Cellular Biochemistry, 2013)

The complete mitogenome and phylogenetic analysis of Bombyx mandarina strain Qingzhou - Xiao-long Hu; Guang-li Cao; Ren-yu Xue; Xiao-jian Zheng; Xing Zhang; Hai-rong Duan; Cheng-liang Gong (Molecular Biology Reports, 2010)

Seasonal variations in heavy metals concentrations in Mt. Qomolangma Region snow - Jianping Duan; Lily Wang; Jiawen Ren; Lun Li; Junqing Han (Journal of Geographical Sciences, 2009)

Hypertonic stimulation induces synthesis and release of glutamate in cultured rat hypothalamic astrocytes and C6 cells - Rong Cao; Shan Jiang; Li Duan; Ying-Fei Xiong; Bei Gao; Zhi-Ren Rao (Neuroscience Bulletin, 2008)

Heterologous expression of vacuolar H+-PPase enhances the electrochemical gradient across the vacuolar membrane and improves tobacco cell salt tolerance - Xiao-Guang Duan; Ai-Fang Yang; Feng Gao; Shang-Li Zhang; Ju-Ren Zhang (Protoplasma, 2007)

Up-regulation of IL-1 receptor type I and tyrosine hydroxylase in the rat carotid body following intraperitoneal injection of IL-1β - Xi-Jing Zhang; Xi Wang; Li-Ze Xiong; Juan Fan; Xiao-Li Duan; Bai-Ren Wang (Histochemistry and Cell Biology, 2007)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)